Cigarette Constituent Health Communications for Smokers: Impact of Chemical, Imagery, and Source. Issue 6 (3rd October 2017) - Kowitt, Sarah D; Sheeran, Paschal; Jarman, Kristen L; Ranney, Leah M; Schmidt, Allison M; Noar, Seth M; Huang, Li-Ling; Goldstein, Adam O
Abstract: Introduction: Communication campaigns are incorporating tobacco constituent messaging to reach smokers, yet there is a dearth of research on how such messages should be constructed or will be received by smokers. Methods: In a 2 × 2 × 2 experiment, we manipulated three cigarette constituent message components: (1) the toxic constituent of tobacco (arsenic vs. lead) with a corresponding health effect, (2) the presence or absence of an evocative image, and (3) the source of the message (FDA vs. no source). We recruited smokers ( N = 1669, 55.4% women) via an online platform and randomized them to one of the eight message conditions. Participants viewed the message and rated its believability and perceived effectiveness, the credibility of the message source, and action expectancies (ie, likelihood of seeking additional information and help with quitting as a result of seeing the message). Results: We found significant main effects of image, constituent, and source on outcomes. The use of arsenic as the constituent, the presence of an evocative image, and the FDA as the source increased the believability, source credibility, and perceived effectiveness of the tobacco constituent health message. Conclusions: Multiple elements of a constituent message, including type of constituent, imagery, and message source, impact their reception among smokers. Specifically, communication campaigns targeting smokers that utilize arsenic as the tobacco constituent, visual imagery, and the FDA logo may be particularly effective in changing key outcomes that are associated with subsequent attitude and behavioral changes. Implications: This article describes how components of communication campaigns about cigarette constituents are perceived. Multiple elements of a tobacco constituent message, including type of constituent, image, and message source may influence the reception of messages among current smokers. Communication campaigns targeting smokers that utilize arsenic as the tobacco constituent, visual imagery, and the FDA logo may be particularly effective in changing key outcomes among smokers. The effects of such campaigns should be examined, as well as the mechanisms through which such campaigns affect change.